“Because our law is our law”: considering Anishinaabe citizenship orders through adoption narratives at Fort William First Nation - Lee, Damien (2017)
This dissertation demonstrates that inherent Anishinaabe (Ojibwe) citizenship law exists, and can be seen through adoption practices used by Anishinaabe families. For more than 165 years, Indigenous citizenship orders have been targeted by Canadian society through its laws, such as the Indian Act and its pre-cursor legislation. As I argue in this dissertation, however, inherent Anishinaabe citizenship law is based on the authority of Anishinaabe families to discern who belongs. By focusing on adoption narratives carried by thirteen knowledge holders from Fort William First Nation (an Anishinaabe community in Ontario, Canada), the dissertation shows that belonging according to inherent Anishinaabe citizenship law is not dependent on the Indian Act or its status logics. Rather, the knowledge holders demonstrate that, when seen through adoption stories, Anishinaabe citizenship is based on values of full inclusion, accountability to community, non-essentialism, and decentralized decision making. This dissertation contributes to literatures concerned with the resurgence of Indigenous citizenship orders, treaty constitutionalism, as well as biskaabiiyang and indigenist research methodologies. October 2017